KONSEP IBNU KHALDUN TENTANG PRODUKSI DALAM EKONOMI ISLAM - Subaidi; Subiyanto (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2020)
Ibn Khaldun discovered many basic economic ideas in the centuriesbefore his birth “officially". He discovered the benefits and necessity ofthe division of labor before Smith and the principle of the value of laborbefore Ricardo. He outlines population theory before Malthus andstresses the role of the state in the economy before Keynes.Ibn Khaldun used concepts to build a dynamic and coherent system. Inthis system, economic mechanisms must bring economic activity tolong-term fluctuations. Because of the coherence of the system,criticisms that can be made against most economic concepts using thesame idea cannot be applied at this time.We must revise the terms of the founding fathers of economic theoriesin the history of economic thought, Ibn Khaldun is claimed to be apioneer for many European scholars, mostly sociologists, historians andphilosophers. However, although his ideas have been known in Europesince the nineteenth century, it seems that his successors were notfamiliar with his economic thinking.